Proton motive force dissipation precludes interaction of microcin J25 with RNA polymerase, but enhances reactive oxygen species overproduction - Dupuy, Fernando G.; Chirou, María V. Niklison; de Arcuri, Beatriz Fernández; Minahk, Carlos J.; Morero, Roberto D. (Biochimica et biophysica acta, 2009)
Microcin J25 targets the RNA polymerase as well as bacterial membranes. Because there is scarce information on the relationship between the uptake and the activity, a fluorescent microcin J25-derivative was used to further characterize its mechanism of action. MccJ25 I13K was labeled with FITC and its uptake by sensitive cells was assessed by fluorescence measurements from supernatants of MccJ25- Escherichia coli suspensions. The interaction of the peptide with bacterial membranes was investigated by fluorescence resonance energy transfer. Oxygen consumption was measured with Clark-type electrode. RNA synthesis was evaluated in vivo by incorporation of [ 3H]uridine. ROS production was assayed by measuring the fluorescence emission of the ROS-sensitive probe 5(and 6)-carboxy-2’,7’-dichlorodihydrofluorescein diacetate. The protonophore 2,4-dinitrophenol decreased 80% of the MccJ25 uptake and prevented inhibition of transcriptional activity, the antibiotic intracellular target. On the other hand, peptide binding to bacterial membranes was not affected and antibacterial activity remained nearly unchanged. Proton gradient dissipation by protonophore accelerated cell oxygen consumption rates and enhanced MccJ25-related reactive oxygen species overproduction. The deleterious reactive oxygen species would be produced as a consequence of the minor fraction of MccJ25 that interacts with the bacterial plasma membrane from the periplasmic side. These results show the first evidence of the mechanism underlying ROS production in sensitive bacteria.